THE IMPORTANCE OF THE HISTORY OF MEDICINE IN INCREASING THE EXCLUSIVE COMPETENCE OF FOREIGN STUDENTS - Komilov, Nodirbek (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article highlights the role of the history of medicine in increasing the exclusive competence of foreign students studying in medical institutions of higher education, and analyzes the formation of the success of teaching the history of medicine and the training of professional specialists in many ways through the study of science.